Emerging Transformations in Tourism and Hospitality - (:unkn) unknown (My University, 2021)
This significant and timely book critically discusses the effects of emerging trends and shifting dynamics on the tourism and hospitality industry at local, regional, national, and international levels in a holistic manner. This book offers a multi-disciplinary and inter-disciplinary approach and examines emerging topics such as technology and disruptive economies as well as the Covid-19 pandemic that are likely to change the future of the industry, either positively or negatively. The book thus advances the knowledge surrounding emergent controversies pertaining to tourism and hospitality including the growth of alternative business models (e.g., sharing economy business models), travel in light of climate change, and human resource ethics given the increasing adoption of artificial intelligence (AI), data, and algorithms. Offering a platform for the critical discussion of pertinent transformations and, as such, providing theoretical and practical insights, this book will be of great value to destination planners, policymakers, industry practitioners, educators, and upper-level students of tourism and hospitality.
Keywords: Tourism; Tourism analysis; Hospitality industry